Mycobacterium bovis BCG recA Deletion Mutant Shows Increased Susceptibility to DNA-Damaging Agents but Wild-Type Survival in a Mouse Infection Model - Sander, Peter (American Society for Microbiology, 2001)
Pathogenic microorganisms possess antioxidant defense mechanisms for protection from reactive oxygen metabolites which are generated during the respiratory burst of phagocytic cells. These defense mechanisms include enzymes such as catalase, which detoxifies reactive oxygen species, and DNA repair systems, which repair damage resulting from oxidative stress. To (i) determine the relative importance of the DNA repair system when oxidative stress is encountered by the Mycobacterium tuberculosis complex during infection of the host and to (ii) provide improved mycobacterial hosts as live carriers to express foreign antigens, the recA locus was inactivated by allelic exchange in Mycobacterium bovis BCG. The recA mutants are sensitive to DNA-damaging agents and show increased susceptibility to metronidazole, the first lead compound active against the dormant M. tuberculosis complex. Surprisingly, the recA genotype does not affect the in vitro dormancy response, nor does the defect in the DNA repair system lead to attenuation as determined in a mouse infection model. The recA mutants will be a valuable tool for further development of BCG as an antigen delivery system to express foreign antigens and as a source of a genetically stable vaccine against tuberculosis.